2021
DOI: 10.3390/land10020219
|View full text |Cite
|
Sign up to set email alerts
|

The Potential to Save Agrestal Plant Species in an Intensively Managed Agricultural Landscape through Organic Farming—A Case Study from Northern Germany

Abstract: Intensive agriculture is among the main drivers of diversity decline worldwide. In Central Europe, pressures related with agriculture include habitat loss due to the consolidation of farming units, pesticide and fertilizer use, and shortened crop rotations. In recent decades, this development has resulted in a severe decline of agrestal plant communities. Organic farming has been suggested as a biodiversity friendly way of farming, as it strongly restricts the use of synthetic pesticides and fertilizers and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The non-parametric ANOVA analysis of variance tests the comparison of variables that have more than two levels (i.e., groups) as well as the simultaneous influence of several factors at once (i.e., MANOVA) with its interaction effects between these factors [96]. Secondly, ANOVA is helpful for multidimensional variables [97]. Thirdly, ANOVA increases statistical power [40].…”
Section: Anova Analysis-concept Advantages and Constraints Of Its Usementioning
confidence: 99%
“…The non-parametric ANOVA analysis of variance tests the comparison of variables that have more than two levels (i.e., groups) as well as the simultaneous influence of several factors at once (i.e., MANOVA) with its interaction effects between these factors [96]. Secondly, ANOVA is helpful for multidimensional variables [97]. Thirdly, ANOVA increases statistical power [40].…”
Section: Anova Analysis-concept Advantages and Constraints Of Its Usementioning
confidence: 99%
“…Agricultural intensification has been identified as the main cause of agrobiodiversity loss (Storkey and Westbury 2007;Potts et al 2010;Meyer et al 2013). Several studies have shown that intensive arable farming negatively affects arable plant communities in terms of their biodiversity as well as the ecosystem services they provide (Marshall et al 2003;Meyer et al 2015;Chamorro et al 2016;Štefanić et al 2019;Görzen et al 2021). The recognition of the importance of the segetal flora for agroecosystems supporting a diverse fauna and beneficial microorganisms has focused attention on the need to maintain traditionally cultivated habitats (Storkey and Neve 2018;Mupepele et al 2019;Böhning-Gaese et al 2020;Bourgeois et al 2020;Gaba et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Measures of weed control prevent successful establishment and seed production of arable weeds. Depending on the strength and effectiveness of weed control, the aboveground vegetation is, therefore, largely controlled by the composition of the seed bank in the soil [17].…”
Section: Introductionmentioning
confidence: 99%